A review on recent advances in implanted medical devices security - Brito, C?sar (2022)
The Implanted Medical Devices (IMD) industry has grown over the past few decades and is expected to grow in the coming ones. Being an asset for the health and quality of life of a patient, the availability of IMD-related products, their increasing complexity and advances in communication capabilities do not seem to have been seamlessly accompanied by cybersecurity concerns. Recent IMD can be integrated in the concept of IoT (Internet of Things) and thus, they are also exposed to attacks impacting on privacy and, above all, on the health and even the life of the device users. While in an early stage of the IMD development, the security procedures were based on the existing classic protocols and models and their functional capabilities were the focus of development, recent efforts have been made to address security from the start. In this paper we review the most recent contributions on the cybersecurity of IMD products and we highlight innovative ideas that represent new design and development paradigms of these devices next generations. In this review it is reinforced that the technological evolution and the progressive access of attackers to resources capable of exploiting multiple vulnerabilities can have a crucial impact in the IMD already implanted in the patient's body, designed to remain in operation for many years. Also, it brings the need to develop novel and robust protocols to guarantee security compatible with constrained computing resources and extremely low energy requirements to be feasible. Finally, the security and privacy concerns regarding this kind of devices should be addressed in the design phase and policies must move from damage mitigation to threat prevention.